The Role of Homeopathy in the History of Epidemics - Cigerli, Oya; İlhan, Fulya (Sağlık Bilimleri Üniversitesi, 2021)
From the earliest ages of civilisation to up until today, epidemic diseases have made great impact on humankind with the mass deaths and economic crisis’ it brought. They created social, political, and economical problems, which have changed the course of history. One of the most important challenges of public health is to control these epidemic outbreaks, which affect many individuals worldwide at the same time. Vaccines, anti-viral medications, and antibiotics are the standard conventional treatments for these diseases. However, the difficulties with developing immunizations, the problem of viral mutations, and the growing issue of antibiotic-resistant bacteria are major obstacles to controlling epidemics. Every epidemic comes with its private symptoms and characteristics; in the course of time until the disease’s agent, treatment and vaccine are found, both economic losses and serious losses of life can be experienced. Homeopathy, is one of the most frequently used and controversial systems of complementary and alternative medicine that is used for the treatment of all kinds of diseases, including the infectious ones for over 200 years. In homeopathy, to choose the right medicine, the physician takes into consideration the organism’s response to the causative factor; the indicated remedy being selected based on the patient’s total symptom picture and not on the cause of disease, means that for starting the treatment, homeopathy does not have to wait until the medical researchers found the cause of the pathology. Therefore, not wasting anytime, it allows a fast and effective response against the epidemic diseases. The purpose of this study is, through the compilation and analysis of historical and epidemiological data and scientific research, to support homeopathy as an option in times of epidemics diseases.

Salgın hastalıklar, insanlık tarihinin en erken dönemlerinden günümüze kadar olan süreçte, neden olduğu yıkımlar ve kitlesel ölümler ile insanlık üzerinde büyük etki bırakmış; yarattıkları sosyal, siyasal ve ekonomik etkiler ile tarihin akışını değiştirmişlerdir. Aynı zamanda, dünyanın pek çok bölgesinde, birçok kişiyi etkileyen bu salgınların kontrol altına alınması, en önemli halk sağlığı problemlerinden biridir. Salgın hastalıklar için konvansiyonel tıp tarafından kullanılan standart tedaviler, aşılar, anti-viral ilaçlar ve antibiyotiklerdir. Diğer yandan, aşı geliştirme sürecindeki zorluklar, virüs mutasyonları ve antibiyotiklere dirençli bakterilerin artması, salgın hastalıkların kontrolü önünde engel oluşturan ana problemlerdir. Her salgın kendine has özellikleri ile gelmekte, etkenin adı konup, etkili tedavi ve aşı bulunana kadar geçen sürede büyük can ve ekonomik kayıplar oluşabilmektedir. Homeopati, en sık kullanılan ve en çok tartışılan alternatif ve tamamlayıcı tedavi disiplinlerinden biridir.200 yılı geçen bir süredir, bulaşıcı ve enfeksiyon hastalıkları dahil, her türlü hastalığın tedavisinde kullanılmaktadır. İlaç seçerken etkeni değil, etkenin kişide oluşturduğu semptomlar bütününü göz önüne alır. Yani tedaviye başlamak için etkenin belli olmasını beklemek zorunda değildir. Bundan dolayı, salgın hastalıklarda vakit geçirmeden hızlı ve etkin bir tedavi seçeneği sunar. Bu yazının amacı, tarihsel ve epidemiyolojik veriler ve yapılan bilimsel araştırmaların derlenmesi ile homeopatinin salgın hastalıklarla mücadele konusunda, bir seçenek olarak bilimsel çalışma ve tedavi programlarına dahil edilmesini desteklemektir.
Homeopatinin Salgın Hastalıklar Tarihindeki Rolü
Keywords: Clinical Sciences; Klinik Tıp Bilimleri